A inconstitucionalidade da redução de terras indígenas no processo demarcatório por caracterizar remoção - Carneiro, Edilton Borges (2006)
This master dissertation of is centered in the analysis of the subject aboriginal lands, searching to understand the paper of the property of the aboriginal land in the civil law and constitutional Brazilian from the promulgation and entrance in vigor of the Constitution of the Federative Republic of Brazil of 1988. The work, leaving of a historical briefing, looks for to understand the treatment given for the legislators Portuguese and Brazilian to aboriginal lands, arguing the concept of property in the culture colonizer occidental person and the aboriginal culture to show the deep difference of as these concepts are worked by these distinct cultures. It still argues the constitutional recognition of the originary right of the aboriginal peoples to the lands that traditionally occupy, and the interpretation given for the legal hermeneutics to the constant constitutional device of article 231, § 1º, of as if it characterizes the tradicionalidade of the occupation, stops from this however, together with the analysis and interpretation of the contained one in article 231, § 5º of the Brazilian Great Letter, to demonstrate to the unconstitutionality of the land reduction aboriginals in the administrative proceeding of landmark, therefore this reduction characterizes removal of the peoples aboriginals of its lands, and not if it inside finds of the definitive situations in numerus clausus, specifically permissive of the removal act. Key Words: aboriginal lands, unconstitutionality, reduction, landmark, removal.